Case analysis and CFD numerical study on gas explosion and damage processing caused by aging urban subsurface pipeline failures. (March 2019) - Wang, Kan; Shi, Tingting; He, Yuru; Li, Mingzhi; Qian, Xinming
Abstract: The overall targets of this study are to focus on a comprehensive summary of the East Harlem gas explosion in Manhattan, New York. To investigate how the tragedy occurs in the neighborhood of Manhattan and how it influences the probability and the scale of this accident causing corresponding damages. CFD numerical simulations were performed to study explosion characteristics of natural gas leakage and the explosion based on the realistic accident scenario. The gas dispersion, blast wave and flame propagation process were analyzed, the simulated results agreed well with actual destruction in real accident. It further verified the location and the reasons of the ignition sources in the actual event. Moreover, a series of post-accident testing and inspections were undertaken on the accident scene, followed by an in-depth analysis of the causes. This accident highlights the potential hazards of aging urban subsurface infrastructure in such historic metropolis, which especially targets at aging pipes. It is intended to prompt a serious discussion concerning the outmoded technology, overburdened lines, maintenance programs and future risk management, which must be properly managed by authorities if NYC is to remain a dominant global urban destination. Highlights: A case study of natural gas leakage and explosion accident in New York was presented and analyzed. CFD numerical method was performed to simulate explosion characteristics based on realistic accident scenario. A series of post-accident testing and inspections were undertook on the accident scene, followed by an in-depth analysis of the causes. Research findings aim to the metropolitan's future, it could seriously undermine the city's economic competitiveness and the quality of life, and lead to substantial long-term costs.